Case Report: Primary Immunodeficiencies, Massive EBV+ T-Cell Lympoproliferation Leading to the Diagnosis of ICF2 Syndrome - Padeira, Gonçalo Luzes; Araújo, Catarina; Cordeiro, Ana Isabel; Freixo, João; Martins, Catarina Gregório; Neves, João Farela (Frontiers in Immunology, 2021)
In immunocompromised patients EBV may elicit B-cell transformation and proliferation. A five- year-old microcephalic boy was admitted with fever and non-malignant polymorphic T-cell lymphoproliferative disease associated with EBV. A presumptive diagnosis of primary immunodeficiency with inability to control EBV was made and next-generation sequencing led to the identification of a novel ZBTB24 mutation (ICF2-syndrome). This case shows that susceptibility to EBV seems to be particular of ICF-2 as it hasn’t been described in the other types of ICF. It is mandatory to raise the hypothesis of an underlying PID in case of severe EBV infection.